PEMBERIAN EKSTRAK BAWANG MERAH SEBAGAI ZAT PENGATUR TUMBUH ALAMI PADA PERTUMBUHAN SETEK LADA (Piper nigrum L.) - Puji Lestari Tarigan; Nurbaiti Nurbaiti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The study aims to determine the effect of concentration of extracts of onion on the growth pepper cuttings and to get the best onion extract concentration. This research has been conducted at the Experimental Farm, Faculty of Agriculture, University of Riau, from February to May 2016. This study used a completely randomized design (CRD), which consist of 5 treatments onion extract (0%, 20%, 40%, 60% and 80%) and four replications. Data were analyzed using ANOVA. Parameters were observed, namely, the percentage of live cuttings, shoots emerging time, shoot length, number of leaves, number of roots, roots length, and root volume. The result showed that the concentration of red onion extract as a natural plant growth regulator had no significant effect on all parameters of the growth pepper cuttings. An onion extract concentration of 60% gives better result in all parameters.Keywords: pepper, pepper cuttings, red onion extract